Toluene Dioxygenase-Catalyzed cis-Dihydroxylation of Quinolines: A Molecular Docking Study and Chemoenzymatic Synthesis of Quinoline Arene Oxides - Boyd, Derek R.; Sharma, Narain D.; Loke, Pui L.; Carroll, Jonathan G.; Stevenson, Paul J.; Hoering, Patrick; Allen, Christopher C. R. (Frontiers in Bioengineering and Biotechnology, 2021)
Molecular docking studies of quinoline and 2-chloroquinoline substrates at the active site of toluene dioxygenase (TDO), were conducted, using Autodock Vina to identify novel edge-to-face interactions and to rationalize the observed stereoselective cis-dihydroxylation of carbocyclic rings and formation of isolable cis-dihydrodiol metabolites. These in silico docking results of quinoline and pyridine substrates, with TDO, also provided support for the postulated cis-dihydroxylation of electron-deficient pyridyl rings, to give transient cis-dihydrodiol intermediates and the derived hydroxyquinolines. 2-Chloroquinoline cis-dihydrodiol metabolites were used as precursors in the chemoenzymatic synthesis of enantiopure arene oxide and arene dioxide derivatives of quinoline, in the context of its possible mammalian metabolism and carcinogenicity.